2017
DOI: 10.1139/facets-2016-0058
|View full text |Cite
|
Sign up to set email alerts
|

Cautions on using the Before-After-Control-Impact design in environmental effects monitoring programs

Abstract: Often the Before-After-Control-Impact (BACI) design is suggested as being a statistically powerful experimental design in environmental impact studies. If the timing and location of the impact are known and adequate pre-data are collected, the BACI design is considered optimal to help isolate the effect of the development from natural variability. This paper presents 9 years of results from a long-term BACI experiment tested using a range of statistical models and post-impact monitoring designs. To explore sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
106
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 30 publications
1
106
0
1
Order By: Relevance
“…Indeed, the short time involved in our study–considering relevant generation time scales for birds–could represent a static picture of local population dynamics. If we could have analyzed more than a single generation, we could have better considered whether the changes we observed were transient or permanent (Smokorowski & Randall ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the short time involved in our study–considering relevant generation time scales for birds–could represent a static picture of local population dynamics. If we could have analyzed more than a single generation, we could have better considered whether the changes we observed were transient or permanent (Smokorowski & Randall ).…”
Section: Discussionmentioning
confidence: 99%
“…Successfully detecting environmental change with monitoring is affected by many factors, including the availability of data from an undisturbed baseline period and the study designs selected (Smokorowski and Randall 2017). Where a baseline data set is missing or deficient, the capability to detect change is compromised and alternative approaches are required.…”
Section: Discussionmentioning
confidence: 99%
“…A primary difficulty in ecological monitoring is the lack of information describing the undisturbed baseline conditions. This information is necessary for a widely discussed and ideal design, before-after-control-impact (BACI; Smokorowski and Randall 2017). Where data to fulfill the BACI design or its variants are not available, other study types such as paleolimnology may be employed (Kurek et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The ideal scenario is to have a BACI (before‐after‐control‐impact) study design (Ogren & Huckins ; Tummers et al ) that controls for both spatial and temporal variation. However, few studies achieve this despite that it has been shown to be the overall superior method for monitoring (Smokorowski & Randall ).…”
Section: Introductionmentioning
confidence: 99%